(untitled) (Bulletin KNOB, 2003)
Traditionally, large-scale and systematic building are the qualities attributed to the urban extensions of Amsterdam. The systematic character of town planning was invariably approached from new perspectives, whereby aesthetic appreciation initially prevailed. The idea of the town as a brilliant total design dates back to the nineteenth century. This idea was presented in various forms, without being based on much substantial research. The extent to which the townscape was designed was presented as far more significant than we would now conclude from examining the facts. This is only to be expected, since the historiography of town planning was strongly related to the contemporary planning practice. Later all sorts of models of orderly laid out (fortified) towns were projected onto the urban extensions of Amsterdam. The fact that fortified towns have an almost exclusively military programme was ignored: in their layout this function was one-sidedly taken into account. Trade, traffic or administration did not play a significant part. However, extension of an existing town was a totally different assignment than laying out a fortified town on an empty site or designing an ’ideal’ town on a piece of paper. The approach to Amsterdam as a derivative of the ideal (fortified) town ignores practical requirements and the fact that the town was part of a larger entity of landscape (subsoil) and infrastructure (roads, harbours, waterways, dikes). Of course rational, orthogonal parcelization, rational street and canal profiles and symmetrical configurations of building blocks and streets are to be found in an ’ideal’ as well as a real town. But if the designers of the Amsterdam town plan had learned anything at all from the treatises, this was probably not the mere copying of urban forms, but rather the combination of beauty and functionality by applying urban planning methods such as orthogonal parcelization and straight streets and canals. Art historians conducting research into town planning were strongly inclined to attribute a normative role to the treatises, to which the object of the research itself was made subordinate. By contrast, the research in the records conducted so far does not point to a theoretically founded, but to a highly pragmatic approach to urban development. Especially the research of Jansen and Van Essen has resulted in very essential insights into the proceedings around the town extensions. However, the urban development cannot just be investigated on the basis of - as yet fragmentary - research in the records. The urban development, the combination of town planning and urbanisation, of subsoil and intervention, cannot merely be explained from the resolutions of the town council and treasurers. A town design is not a work of art in its own right, but a solution to a series of problems in a specific situation.